Identifying the ‘Active Ingredients' of an Effective Psychological Intervention to Reduce Fear of Cancer Recurrence: A Process Evaluation - Kan, Janice M.; Dieng, Mbathio; Butow, Phyllis N.; Mireskandari, Shab; Tesson, Stephanie; Menzies, Scott W.; Costa, Daniel S. J.; Morton, Rachael L.; Mann, Graham J.; Cust, Anne E.; Kasparian, Nadine A. (Frontiers in Psychology, 2021)
Purpose: Psychological interventions targeting fear of cancer recurrence (FCR) are effective in reducing fear and distress. Process evaluations are an important, yet scarce adjunct to published intervention trials, despite their utility in guiding the interpretation of study outcomes and optimizing intervention design for broader implementation. Accordingly, this paper reports the findings of a process evaluation conducted alongside a randomized controlled trial of a psychological intervention for melanoma patients. Methods: Men and women with a history of Stage 0–II melanoma at high-risk of developing new primary disease were recruited via High Risk Melanoma Clinics across Sydney, Australia and randomly allocated to receive the psychological intervention (n = 80) or usual care (n = 84). Intervention participants received a tailored psycho-educational resource and three individual psychotherapeutic sessions delivered via telehealth. Qualitative and quantitative data on intervention context, processes, and delivery (reach, dose, and fidelity), and mechanisms of impact (participant responses, moderators of outcome) were collected from a range of sources, including participant surveys, psychotherapeutic session audio-recordings, and clinical records. Results: Almost all participants reported using the psycho-educational resource (97%), received all intended psychotherapy sessions (96%), and reported high satisfaction with both intervention components. Over 80% of participants would recommend the intervention to others, and a small proportion (4%) found discussion of melanoma-related experiences confronting. Perceived benefits included enhanced doctor-patient communication, talking more openly with family members about melanoma, and improved coping. Of potential moderators, only higher FCR severity at baseline (pre-intervention) was associated with greater reductions in FCR severity (primary outcome) at 6-month follow-up (primary endpoint). Conclusions: Findings support the acceptability and feasibility of a psychological intervention to reduce FCR amongst individuals at high risk of developing another melanoma. Implementation into routine melanoma care is an imperative next step, with FCR screening recommended to identify those most likely to derive the greatest psychological benefit.